Pazopanib Enhances Paclitaxel-Induced Mitotic Catastrophe in Anaplastic Thyroid Cancer - Isham, Crescent R. (2013)
Anaplastic thyroid cancer (ATC) has perhaps the worst prognosis of any cancer, with a median survival of only about 5 months regardless of stage. Pazopanib monotherapy has promising clinical activity in differentiated thyroid cancers (generally attributed to vascular endothelial growth factor receptor inhibition), yet has less effective single-agent activity in ATC. We now report that combining pazopanib with microtubule inhibitors such as paclitaxel produced heightened and synergistic antitumor effects in ATC cells and xenografts that were associated with potentiated mitotic catastrophe. We hypothesized that combined effects may reflect enhanced paclitaxel-induced cytotoxicity mediated by cell cycle regulatory kinase inhibition by pazopanib. Indeed, pazopanib potently inhibited aurora A, with pazopanib/paclitaxel synergy recapitulated by aurora A short hairpin RNA knockdown or by specific aurora A pharmacological inhibition. Pazopanib/paclitaxel synergy was reversed by aurora A knockdown. Moreover, aurora A (but not B or C) message and protein levels were significantly increased in patient ATCs, and durable benefit resulted from pilot clinical translation of pazopanib/paclitaxel therapy in a patient with metastatic ATC. Collectively, these results suggest that the pazopanib/paclitaxel combination is a promising candidate therapeutic approach in ATC and that aurora A may represent a potentially viable therapeutic molecular target in ATC.